Silver Ferns of Bangladesh and the exclusion of reported Aleuritopteris grisea (Blanf.) Panigrahi (Pteridophyta, Pteridaceae) - Jenkins, CR Fraser (Bangladesh Journal of Botany, 2014)
The three species of Aleuritopteris ("Silver Ferns") present in Bangladesh are discussed, A. bicolor (Roxb.) Fraser-Jenk, A. anceps (Blanf.) Panigrahi and A. subdimorpha (C.B.Clarke & Baker) Fraser-Jenk., correcting some previous erroneous reports. Aleuritopteris grisea (Blanf.) Panigrahi has recently been reported from the Chittagong Hills, S.E. Bangladesh. But that species is well known to be a high Himalayan Sino-Himalayan species of the Tibetan subtype, confined to the main Himalayan ranges and occurring from c. 2900 - 4000 m altitude. The specimen misreported as it from Bangladesh belongs to the low-altitude species, A. anceps (Blanf.) Panigrahi, which occurs from c. 300-750 m altitude and is a S.E. Asian (Malesian) element in the flora of the Indian subcontinent. This species was first knowingly collected in Bangladesh in the same District in 2003 by the present author, but unfortunately Bangladesh was then inadvertently omitted from its range in his monographic summary of Indian subcontinental cheilanthoid ferns. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18020 Bangladesh J. Bot. 42(2): 195-206, 2013 (December)